Does altitude have an effect on stroke mortality and hospitalization risk? A comprehensive evaluation of United States data - Gerken, Jacob; Huber, Nathan; Zapata, Demi; Barron, Ileana G.; Zapata, Isain (Frontiers in Stroke, 2023)
Background: Globally, stroke is a leading cause of death among people over 50 years of age. In the United States alone over 150,000 die of a stroke every year. Environmental factors such as altitude may play a role in these outcomes; however, their effects have not yet been comprehensively explored. The objective of this study is to evaluate the effect of altitude along other covariates on stroke mortality and hospitalization rates in adults. Methods: This study utilized altitude, stroke mortality and hospitalization rates, anti-hypertensive and cholesterol lowering medication usage, smoking prevalence, and sociodemographic data (MH-SVI) for 3,141 counties in the United States from 2018 to 2020 obtained from government databases. Data were analyzed using generalized additive models with and without adjustments for covariates. Results: Unadjusted models show that altitude has a comparable significant negative effect on mortality rates for Black and White populations. When including all covariates, altitude continues having a significant protective effect against stroke fatalities to White populations (retaining 26.6% and 53.8% of the effect magnitude for CVD and stroke mortality respectively), a non-significant effect to the Black population and a detrimental effect for Hispanic and Asian Pacific populations for CVD mortality (a 21.6% and 39.1% effect increase respectively). Conclusions: Our findings add to the growing body of evidence that environmental factors add to disparities and play a significant role in CVD and stroke mortality. The effect of altitude is comparable in size to smoking, medication usage, and social determinants of health.